An Empirical Examination of the Perceived Quality of Fruits - Sulé Alonso, Aránzazu; Lévy Mangin, Jean- Pierre (CIENCIA ergo-sum; Vol. 5 Núm. 3 (1998): CIENCIA ergo-sum (noviembre 1998-febrero 1999), 2017)
This paper deals with the issue of analyzing quality fruits consume preferences in order to determinate the effects of intrinsic versus extrinsic clues in the perceptions of quality. The author built and developed a Perceived Quality Model. It shows a quantitative estimation of the Perceived Quality Model in the analysis of quality perceptions of food such as fruit.